Primitive Man: Traditional and Modern Interpretation - Gendrolis, Edmundas (Problemos, 1989)
The article deals with the changes which took place in the understanding of the primitive man under the influence of the new archaeological and paleoanthropological discoveries. The traditional view, according to which man was a very weak creature and lived in herds just until the appearance of the modern man is questioned. To the contrary it is showed that already Neanderthal (paleoanthropians) lived in communities, and help and care for their kinsmen alive and dead was dominant in their relations. Further, it is said that consciousness was developed up to the level that religious views and rites originated. The author of the article even finds the grounds to suppose that in this stage of human development the attempts of counting were made and the aesthetic feeling has manifested itself.